Two new genera, ten new species and new records of Amazonian Stygnidae Simon, 1879 (Opiliones: Laniatores) - Pinto-Da-Rocha, Ricardo; Tourinho, Ana Lúcia (Zootaxa, 2012)
As a result of recent expeditions to two mountains in the Amazon basin, Tapirapecó and Pico da Neblina, two new genera ofStygnidae, Imeri g. nov. (type species Imeri lomanhungae sp. nov.) and Jime g. nov. (type species Jime chifrudo sp. nov.), andten new species are described: Auranus hehu sp. nov., Auranus tepui sp. nov., Imeri lomanhungae sp. nov.; Jime chifrudo sp.nov.; Stygnoplus ianomami sp. nov.; Stygnus magalhaesi sp. nov.; Stygnoplus neblina sp. nov.; Stygnoplus tapirapeco sp. nov.;Stygnus nogueirai sp. nov., Stygnus kuryi sp. nov.. Additionally, new distributional records in Amazonas (Brazil) are presentedfor Stygnidius guerinii Soerensen, 1932, Minax tetraspinosus Pinto-da-Rocha, 1997 and Protimesius longipalpis (Roewer, 1943). Keys for genera of Heterostygninae and Stygninae are provided.